1999
DOI: 10.1021/ma990999e
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic Behavior of Semidilute Solutions of Multisticker Polymer Chains

Abstract: Multisticker polymer chains consisting of water-soluble polyacrylamides hydrophobically modified with low amounts of N,N-dihexylacrylamide have been prepared by a free radical micellar polymerization technique. This process gives multiblock copolymers in which the number and length of the hydrophobic blocks can be tuned by varying the surfactant over hydrophobe molar ratio. The viscoelastic behavior of semidilute solutions of various series of copolymers with variable molecular weights (M w ≈ 4.2 × 104−2.7 × 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
224
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 227 publications
(248 citation statements)
references
References 51 publications
(145 reference statements)
23
224
1
Order By: Relevance
“…The viscosity of PDA-4 solution was higher than that of PDA-1 solution at the concentration above C * (0.30 g/dl), opposite tend was showed at the concentration below C * . This result indicated that PDA prepared with template exhibited a longer hydrophobic block characteristic, which made it more easily to form intermolecular association at the concentration above C * and intramolecular association at the concentration below C * [8,33,34]. It was interesting to note that the viscosity of PDA was higher than that of PAM without hydrophobically modified at the concentration below C * .…”
Section: Apparent Viscosity Of Different Polymer Solutionsmentioning
confidence: 92%
“…The viscosity of PDA-4 solution was higher than that of PDA-1 solution at the concentration above C * (0.30 g/dl), opposite tend was showed at the concentration below C * . This result indicated that PDA prepared with template exhibited a longer hydrophobic block characteristic, which made it more easily to form intermolecular association at the concentration above C * and intramolecular association at the concentration below C * [8,33,34]. It was interesting to note that the viscosity of PDA was higher than that of PAM without hydrophobically modified at the concentration below C * .…”
Section: Apparent Viscosity Of Different Polymer Solutionsmentioning
confidence: 92%
“…In all cases, the incorporation level of DiHexAM was nearly complete ( Table 1) as was already found for hydrophobically modified poly(acrylamides). [7,11,12,15,22,23,30] Several attempts to determine the hydrophobe incorporation level in the samples from series 3 were unsuccessful. The use of D 2 O, and its mixture with deuterated methanol or deuterated DMSO did not allow us to detect the signal of hydrophobic units protons in the spectrum.…”
Section: Copolymer Compositionmentioning
confidence: 99%
“…where N Agg is the aggregation number of the surfactant, CMC is its critical micelle concentration, f HM is the mole fraction of HM in the comonomer feed, and N is the chain length of polymer [53]. Because incorporation of a small amount of hydrophobic groups in a hydrophilic polymer backbone results in polymers with extraordinary rheological properties in aqueous solutions, many studies have been carried out during the past two decades on the synthesis and solution properties of hydrophobically modified hydrophilic polymers [54,55].…”
Section: Preparation Of Hydrophobically Modified Hydrogelsmentioning
confidence: 99%